Repetition In Anuar Nor Arai's Vacuum - Mas Rynna Wati Ahmad (Fakulti Sains Sosial dan Kemanusiaan, 2013)
One of the most significant features in dramatic conversation in Theatre of the Absurd is repetition. The technique is to signify the nonsensical dialogue as a form of communication between people which is perceived to be futile. It is a common marker for any absurd play to indicate that too many words lead to more confusion thus leading us far away from understanding the significant philosophical underpinnings. This paper intends to focus on the appropriation of absurd techniques which is the repetition of words and phrases experimented by the late Anuar Nor Arai in his play, Vacuum during the period of Experimental Theatre. It examines the technique used that is applicable to the theatre in Malaysia, especially in relation to the local social changes and political scenarios. His experimentation had given an insight of a soul who is confused and lost in finding his identity in a vortex of change in Malaysia’s new, restructured society.